A proteção do direito à paisagem urbana pelo sistema interamericano de direitos humanos - Barrios, Anelise Barboza (2015)
The following study, tries to show and to explain strategies for the right of urban landscaping through the system of the Inter-American Court of Human Rights, specially through advice and law sentences. That´s because precedent could occasionatean a possible legislative developments in the domestic sphere which may enable an effective protection of this right in Brazil. Therefore, it is proposed to answer the following question: considering the failure of the Brazilian State to provide sufficient legal and regulatory instruments to the effective protection of the urban landscape in Brazil, is it possible to outline a contentious insertion strategy this right for Inter-American Human Rights? The approach method was deductive, because part of assumptions already consolidated and, adding to the procedure technique which stresses highlights an analysis of the cases before the system as well as an exhibition of laws dealing about the landscape in Brazil, this descriptive research emerges from two sides. Initially explores the evolution of the thematic agenda of the Inter-American Human Rights passing of the States Parties to demand an active role in the production of social equilibrium. After , studying strategically the right to urban landscape , seeking unveil it as a human right and ratify it in the list of fundamental rights, locating it on the concepts of environment, culture, space, checking the subjectivity that encompasses the theme from the perspective of Milton Santos . The results confirmed the possibility of indirect insertion of the theme in the system by asserting possible violations of civil and political rights under the American Convention as effective judicial protection, due process, mental integrity and access to information that may ensure protection reflective urban landscape within the system and may lead to an evolution of the theme in the legislative environment in Brazil.